Microbiome in urologic neoplasms: focusing on tumor immunity - Jun Zou; Baisheng Xu; Hongbing Gao; Peiyue Luo; Tao Chen; Huanglin Duan (Frontiers in Immunology)
Urological tumors are an important disease affecting global human health, and their pathogenesis and treatment have been the focus of medical research. With the in - depth study of microbiomics, the role of the microbiome in urological tumors has gradually attracted attention. However, the current research on tumor - associated microorganisms mostly focuses on one type or one site, and currently, there is a lack of attention to the microbiome in the immunity and immunotherapy of urological tumors. Therefore, in this paper, we systematically review the distribution characteristics of the microbiome (including microorganisms in the gut, urine, and tumor tissues) in urologic tumors, the relationship with disease prognosis, and the potential mechanisms of microbial roles in immunotherapy. In particular, we focus on the molecular mechanisms by which the microbiome at different sites influences tumor immunity through multiple “messengers” and pathways. We aim to further deepen the understanding of microbiome mechanisms in urologic tumors, and also point out the direction for the future development of immunotherapy for urologic tumors.